Features of formation and identification of sparingly soluble and coordination compounds of polyhexametyleneguanidine with Pb(ІІ), Cd(ІІ), Cu(ІІ), Zn(ІІ) in aqueous solutions - Yanushevskaya, Elena; Suprunchuk, Vladimir; Buket, Olexander; Ivanyuk, Olena (Eastern-European Journal of Enterprise Technologies, 2016)
Existing methods of water treatment are faced with the problem of accompanying secondary contaminants introduced by the process of purification or neutralization of the primary contaminants. Polyhexamethyleneguanidine (PHMG) is effective for heavy metals ions removal and reduces environmental pollution. The efficiency of polyhexamethyleneguanidine as a complexing agent, biocide and flocculant is directly related to the ability to bind heavy metal ions, and the stronger the metal aggregates with the polyelectrolyte, the better the water purification and the easier the precipitation. The assumption was confirmed about the complex reaction of polyhexamethyleneguanidine with ions of heavy metals (Pb, Cd, Cu, Zn), the features of which are determined by the electron configuration of these metals: Pb(II) and Cd(II) are characterized by the formation of associates on the basis of sparingly soluble basic salts, and the direct coordination reaction of the metal ion with the PHMG nitrogen is more characteristic of Cu(II) and Zn(II). The products of the reaction of salts of heavy metals (Pb, Cd, Cu, Zn) with polyhexamethyleneguanidine were investigated by IR spectroscopy. The bonds, confirming the formation of stable compounds were revealed in the samples. The level of bond strength and the method of metal binding with polyelectrolyte were studied by polarography. The stability constants and coordination numbers of coordination compounds were computed, which allows predicting their stability in the process of technological transformations. This makes it possible to recommend PHMG for use in multistage processes of water purification from heavy metals.